Safety and efficacy of subcutaneous tocilizumab in systemic sclerosis: results from the open-label period of a phase II randomised controlled trial (faSScinate). Issue 2 (24th October 2017) - Khanna, Dinesh; Denton, Christopher P; Lin, Celia J F; van Laar, Jacob M; Frech, Tracy M; Anderson, Marina E; Baron, Murray; Chung, Lorinda; Fierlbeck, Gerhard; Lakshminarayanan, Santhanam; Allanore, Yannick; Pope, Janet E; et al.
Abstract : Objectives: Assess the efficacy and safety of tocilizumab in patients with systemic sclerosis (SSc) in a phase II study. Methods: Patients with SSc were treated for 48 weeks in an open-label extension phase of the faSScinate study with weekly 162 mg subcutaneous tocilizumab. Exploratory end points included modified Rodnan Skin Score (mRSS) and per cent predicted forced vital capacity (%pFVC) through week 96. Results: Overall, 24/44 (55%) placebo-tocilizumab and 27/43 (63%) continuous-tocilizumab patients completed week 96. Observed mean (SD (95% CI)) change from baseline in mRSS was –3.1 (6.3 (–5.4 to –0.9)) for placebo and –5.6 (9.1 (–8.9 to–2.4)) for tocilizumab at week 48 and –9.4 (5.6 (–8.9 to –2.4)) for placebo-tocilizumab and –9.1 (8.7 (–12.5 to –5.6)) for continuous-tocilizumab at week 96. Of patients who completed week 96, any decline in %pFVC was observed for 10/24 (42% (95% CI 22% to 63%)) placebo-tocilizumab and 12/26 (46% (95% CI 27% to 67%)) continuous-tocilizumab patients in the open-label period; no patients had >10% absolute decline in %pFVC. Serious infection rates/100 patient-years (95% CI) were 10.9 (3.0 to 27.9) with placebo and 34.8 (18.0 to 60.8) with tocilizumab during the double-blind period by week 48 and 19.6 (7.2 to 42.7) with placebo-tocilizumab and 0.0 (0.0 to 12.2) with continuous-tocilizumab during the open-label period. Conclusions: Skin score improvement and FVC stabilisation in the double-blind period were observed in placebo-treated patients who transitioned to tocilizumab and were maintained in the open-label period. Safety data indicated increased serious infections in patients with SSc but no new safety signals with tocilizumab. Trial registration number: NCT01532869; Results.